Kompetencje uczniów niesłyszących i słabosłyszących w zakresie posługiwania się językiem angielskim w szkołach podstawowych, gimnazjach i szkołach ponadgimnazjalnych - Domagała-Zyśk, Ewa (Neofilolog, 2011)
Teaching foreign languages to the deaf formally started in Poland in 2001 so it still can be treated as a relatively new educational phenomenon that needs to be thoroughly researched. So far there have been only several works in the literature that would present the approaches, methods and techniques that the teachers might use. However, there is not a single study that would touch upon the problem of the effectiveness of the teaching programs. The aim of the paper is to explore the linguistic competencies of the deaf students of Polish primary, low secondary (gymnasium) and sec-ondary schools as far as their reading comprehension, vocabulary and grammar competencies and communicative skills are concerned. On the basis of these analyses and contemporary knowledge about the principles of teaching foreign languages to the deaf (cf. Domagała-Zysk 2001, 2003, 2010 and others) a document is presented, Linguistic competences of the hearing-impaired students in the foreign language classroom, that might serve as a significant contribution to our knowledge about the effectiveness of foreign language education for deaf students.